The cost effectiveness of teriparatide as a first-line treatment for glucocorticoid-induced and postmenopausal osteoporosis patients in Sweden - Murphy Daniel R; Smolen Lee J; Klein Timothy M; Klein Robert W (BMC Musculoskeletal Disorders, 2012)
Abstract Background This paper presents the model and results to evaluate the use of teriparatide as a first-line treatment of severe postmenopausal osteoporosis (PMO) and Glucocorticoid-induced osteoporosis (GIOP). The study’s objective was to determine if teriparatide is cost effective against oral bisphosphonates for two large and high risk cohorts. Methods A computer simulation model was created to model treatment, osteoporosis related fractures, and the remaining life of PMO and GIOP patients. Natural mortality and additional mortality from osteoporosis related fractures were included in the model. Costs for treatment with both teriparatide and oral bisphosphonates were included. Drug efficacy was modeled as a reduction to the relative fracture risk for subsequent osteoporosis related fractures. Patient health utilities associated with age, gender, and osteoporosis related fractures were included in the model. Patient costs and utilities were summarized and incremental cost-effectiveness ratios (ICERs) for teriparatide versus oral bisphosphonates and teriparatide versus no treatment were estimated. For each of the PMO and GIOP populations, two cohorts differentiated by fracture history were simulated. The first contained patients with both a historical vertebral fracture and an incident vertebral fracture. The second contained patients with only an incident vertebral fracture. The PMO cohorts simulated had an initial Bone Mineral Density (BMD) T-Score of −3.0. The GIOP cohorts simulated had an initial BMD T-Score of −2.5. Results The ICERs for teriparatide versus bisphosphonate use for the one and two fracture PMO cohorts were €36,995 per QALY and €19,371 per QALY. The ICERs for teriparatide versus bisphosphonate use for the one and two fracture GIOP cohorts were €20,826 per QALY and €15,155 per QALY, respectively. Conclusions The selection of teriparatide versus oral bisphosphonates as a first-line treatment for the high risk PMO and GIOP cohorts evaluated is justified at a cost per QALY threshold of €50,000.